PENCARIAN OBAT PADA APOTEK TERDEKAT DENGAN MEMANFAATKAN GOOGLE MAP - Anggriawan, Digga; Retnowati, Nurcahyani Dewi (Compiler, 2014)
The availability of drugs at any pharmacy vary different so make customers is not easy get drugs that needed when we comes to pharmacy. We need a system to assist search for drugs. This study use ssimulation of three pharmacy  integrated to web server for synchronize drug stocks. This system needed the coordinates pharmacy and the coordinates customers to perform distance calculations. A data coordinates pharmacy contained in web server while the customer location input to system later request to google map for get the coordinates. Distance calculation method use calculation function code program google map is open source based on the coordinates pharmacy and the coordinates customers who later produce distance is 7,1 Km, 2,1 Km, and 5,8 Km. Than we get produce shortest distance using min method in math object provided the carrier object javascript with percentace is 43,3%, 14%, and 36,6%, and than shortest distance is 2,1 Km with percentace is 14%.